A pedagogy of memory-action (Olhares, 2015)
A pedagogy and an auto pedagogy of the actor must primordially: neither simply deny the corporal doxes and singular clichés on the search for an interior essence nor on the belief in a supra-conscience, but consider the use of them. In this way, the actor could, in his corporal immanence, overflow these doxes in themselves and enter an experimentation zone of new artistic constructions and compositions. To clean the corporal doxes, on this case, does not mean to delete them, but compose and recompose other powers and intensities with themselves. This article is about these questions in its conceptual level along with the examples from a joint of possible practices for a poetical and ethical acting.
Keywords: Happening; Cliché; Memory; Paradox